Penetration of Muamalah Jurisprudence into Indonesian Law - Husni, Husni; Khairat, Miftahul (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims to elaborate the penetration of fiqh muamalah into the Indonesian legal system, especially in laws and regulations related to Islamic financial institutions. One fact is that the nomenclature of muamalah and/or fiqh muamalah is not found at all in legislation and legal system. However, in other reality, substantively, fiqh muamalah has become an integral part of the Indonesian legal system, at least as evidenced by the positivization of fourteen laws and regulations related to Islamic financial institutions. The study uses a descriptive qualitative method that focuses on the analysis of legal documents. The analysis method used is a normative descriptive technique involving a historical approach to Islamic law in the context of Indonesia. The findings of this study reveal that the penetration of fiqh muamalah into the Indonesian legal system does not only occur at the theoretical level, but has also had a real impact on the legal culture, legal structure, and legal substance of Indonesian law. At the level of legal culture, muamalah has become an attitude and legal awareness in the form of beliefs, values, ideas, and expectations of the community. As a legal structure, muamalah already has state institutions and their enforcement organizations. In addition to the House of Representatives, which carry out the role of legislation with the government, the legal norms of muamalah have been implemented by Islamic banking institutions, Islamic capital markets, Islamic insurance, Islamic pawnshops, and other Islamic microfinance institutions. Meanwhile, in terms of legal substance, the legal norms of muamalah have manifested into various laws and regulations related to economic and social activities, which are basically related to the determination of sharia principles as the main reference for the activities of financial institutions, the use of muamalah contracts in sharia economic activities, and the criminalization of violations of sharia principles.